Improving consumer mobility in the mobile voice services market: a comprehensive set of remedies - Ana Amante; Jo\~ao Vareda (International Telecommunications Society (ITS), 2010)
Switching costs increase the rigidity of consumers demand and lessen competition between firms, effects that are particularly relevant in the mobile voice services market. This paper characterizes the most important mobility restrictive factors for consumers in this market, presenting specific examples and discussing their impact on competition. In addition, a survey was conducted to obtain data on consumption decisions by mobile voice customers in Portugal. The survey results suggest that switching costs represent more than 13 euros or 57% of the average monthly expenditure with these services. The disclosure of a new mobile phone number is the most difficult task in the switching process. Customers also showed high concern with respect to the possibility of losing quality of service. Compatibility costs also impose high restrictions to customer mobility. Following the identification of these restrictive factors, the adoption by policy makers of remedies to address the different search and switching costs is discussed and their implementation prioritized according to mobile customers' needs.
Keywords: D18; L51; L96; 330; Switching costs; search costs; remedies